In vitro measurement of temperature changes during implantation of cemented glenoid components - Raiss, Patric; Pape, Guido; Jäger, Sebastian; Loew, Markus; Bitsch, Rudi G.; Rickert, Markus (Acta orthopaedica, 2010)
Background and purpose It is unclear whether the increase in temperature during cement curing may cause osteonecrosis, leading to loosening of the glenoid component in shoulder arthroplasty. We therefore analyzed the temperature during implantation of cemented glenoid implants. Methods 8 keeled and 8 pegged glenoids were implanted in standardized fashion in 8 pairs of scapulas. Temperature and pressure sensors were implanted at the bone-cement interface in the glenoid. Real-time measurements were made of temperature and pressure within the glenoid vault. Results In no case was the temperature reached high enough to endanger the surrounding bone. The mean increase in temperature was 5° (0.5-6.9) in the keeled group and 2.7° (1.7-3.6) in the pegged group. The mean maximum pressure in the keeled group was 50 kPa (20-100) and in the pegged group it was 113 kPa (60-181). Both differences were statistically significant. Interpretation The temperatures that occur during implantation of cemented components are low and probably not high enough to cause osteonecrosis in the surrounding bone.
Gesehen am 10.05.2023